Peculiarities of sustainable cultural development: A case of dark tourism in Lithuania - Virginija Jureniene; Martynas Radzevicius (Journal of Risk and Financial Management, 2022)
The aim of this article is to reveal the connection and significance of the concepts of dark tourism and sustainable tourism for the sustainable development of tourism, especially for regional tourism growth. The article discusses the theoretical aspects of dark tourism and details the aspects of this tourism industry as part of cultural tourism. The article also analyses principles and models of sustainable tourism development, with a stronger focus on the integrated development paradigm. As a relatively significant part of the research and analysis of sustainable tourism is more focused on the challenges posed by global mass tourism, this article focuses on the issues of sustainable development of niche tourism in relation to regional tourism. The article presents the analysis of Lithuanian dark tourism resources, presents the most common dark (dissonant) heritage objects, as well as the evaluation of resources according to the spectrum of dark tourism and the comparative analysis of the country's most popular dark tourism objects from the point of view of sustainable tourism. A qualitative study revealed that regional tourism in Lithuania (especially niche, such as dark tourism) lacks integrity among different stakeholders, especially in involving the local community in the processes of cultural heritage protection and cultural tourism development and in developing more intensive links with the private sector. On the other hand, the analysis also revealed that there is an ambiguous public opinion regarding the dark heritage, which does not contribute to the sustainable development of tourism and the actualization of such heritage. The article also discusses the models of sustainable development of dark tourism and invites to discuss how to encourage greater public involvement in the development of dark tourism as part of cultural tourism, so that the principle of sustainable tourism does not remain an empty declaration.
Keywords: 650; cultural heritage management; dark tourism; sustainable development; sustainable tourism development; tourism; tourism industry development